Modified Novikov Operators and the Kastler-Kalau-Walze-Type Theorem for Manifolds with Boundary - Sining Wei; Yong Wang (Advances in Mathematical Physics)
In this paper, we give two Lichnerowicz-type formulas for modified Novikov operators. We prove Kastler-Kalau-Walze-type theorems for modified Novikov operators on compact manifolds with (respectively without) a boundary. We also compute the spectral action for Witten deformation on 4-dimensional compact manifolds.